2017
DOI: 10.1111/1365-2435.12867
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence in a long‐lived ectothermic vertebrate is temperature dependent but shows no decline in older adults

Abstract: Summary Temperature affects nearly all aspects of the physiology of ectotherms, including their ability to mount an immune response. Typically, the ectothermic vertebrate immune system can respond over a wide range of temperatures, but there is a species‐specific temperature at which responses are strongest, with impaired responses above and below this threshold. In long‐lived ectotherms, ageing could also influence the ability to respond to temperature changes as immunosenecence, the functional decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Palm Beach, 45 km north of Boca Raton, has average temperatures of 28 • C during the hottest month of the year, and 18.6 • C during the coolest month of the year (https://en.climate-data.org). Temperatures outside the range for which ectotherms are adapted to can be expected to result in suboptimal immune function (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Palm Beach, 45 km north of Boca Raton, has average temperatures of 28 • C during the hottest month of the year, and 18.6 • C during the coolest month of the year (https://en.climate-data.org). Temperatures outside the range for which ectotherms are adapted to can be expected to result in suboptimal immune function (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The ectotherm immune system relies on the temperature-dependent activity of enzymes and cells, and immune performance is therefore also constrained by temperature. Although the number of studies on the thermal performance of the ectotherm immune system is limited, immune activity generally conforms to a classic thermal performance curve and operates over a wide range of temperatures (Butler et al, 2013;Ferguson et al, 2016;Graham et al, 2017;Murdock et al, 2012;Zimmerman et al, 2017).…”
Section: Thermal Dependence Of Ectotherm Immunitymentioning
confidence: 99%
“…Studies on sliders have found characteristics of a NAb response, including an age‐related increase in both total antibody levels and antigen‐specific antibody levels and an ability to bind to novel antigens (Zimmerman, Paitz, Vogel, & Bowden, , ). Further, the B cells in the slider turtle are believed to be similar to the B‐1 subset, which maintain function with age (Zimmerman et al., , ). However, it is unknown how the slider uses these NAbs in response to potential pathogens.…”
Section: Introductionmentioning
confidence: 99%